A study of selected physiological and biomechanical variables and effect of a conditioning programme on running performance following main objectives. - Kumar, A.; Verma, S. K.
The effect of three months of the conditioning programme on selected physiological and biomechanical variables of 3000m running performance has been evaluated by applying analysis of variance (ANOVA) and Scheffe post hoc test has been used to identify the location of significant differences between various groups. As a result of the administration of conditioning programme significant improvement have been observed in the heart rate responses in both males and females to bicyclic ergometric exercise as well as to running in the track. Although improvements have been observed in both Vo2 max and submaximal heart rate responses, but the submaximal heart rate improvements seem to be more important than the improvements noticed in maximal exercise capacity indicators. A similar analysis of the effect of conditioning programme on various biomechanical variables revel a significant impact on lap timings, angles of knee, thigh,shank and stride and shoulder swing times. The conditioning programme has resulted in significant changes in the abilities of both male and female runners to lift their knee and thigh with respect to the ground. And increase in stride time as well as shoulder swing time has also been features associated with this conditioning programme. The improvements of various lap times and 3000m performance time reasonably suggest that the conditioning programme has caused self optimization processes to develop movement patterns that require minimum energy and exerts less stress to the body. It is possible that self optimization of biomechanics of running style act as a fine tuning device to both energy expenditure and performance much in the same way that specific training regimen fine tune the physiological system.Both males and females respond to the conditioning programme though with varying magnitudes in terms of their morpho-physiological and biomechanical responses. Finally, it is thought that the conditioning programme because of its long duration and specific constituents like stretching, aerobic and speed components, has been successful in producing the requisite biomechanical and physiological changes and thus running economy.